Abkhazian families in KemalPasha - Keskin, Mehmet Ali (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
The lack of research on Abkhazian families residing in the Artvin region of the Republic of Turkey, both within Georgian and Turkish academia, highlights the novelty of this paper. Specifically focusing on the Abkhazian families in Kemal Pasha district of Artvin province, this study offers valuable insights. Situated near the border of Georgia, Kemal Pasha district (Ilche) is a coastal area along the Black Sea, with the city of Kemal Pasha serving as its administrative center. The district predominantly consists of Laz and Hemsins populations. district of Artvin province, this study offers valuable insights. Situated near the border of Georgia, Kemal Pasha district (Ilche) is a coastal area along the Black Sea, with the city of Kemal Pasha serving as its administrative center. The district predominantly consists of Laz and Hemsins populations. Of particular interest is the presence of two Abkhazian families residing in the city of Kemal Pasha, as there are no concentrated settlements of Abkhazian descendants in Artvin province. However, traces of Ab-khazian ancestral memory can be observed among the contemporary population. The primary reason behind individual cases of Abkhazian settlement in the region can be attributed to emigration. It is noteworthy that during the era of emigration, Artvin served as a significant transit point for North Caucasian migrants en route to Erzurum, a major collection and distribution center. The timeliness of this topic is further emphasized by the fact that the brothers under examination are descendants of Abkhazians who settled in the Batumi district in the mid to late 19th century before they emi-grated from Abkhazia. The study of Caucasian migration is an important area within modern scientific re-search, and part of this research involves observing the faint traces of these migrations within Artvin province. An essential aspect of this study is the recognition that Kemal Pasha is a coastal settlement where the first-generation Abkhazians were engaged in seafaring activities. They transported cargo within the vicinity, with their sailing routes encompassing Khofa, Batumi, and occasionally Trabzon under favorable weather conditions. This maritime activity persisted until the 1920s. Despite the limited available information regard-ing the memory of Abkhazians in Kemal Pasha, this paper aims to analyze their family history within the context of Caucasian migrations. It is worth noting that the closest concentration of Abkhazians to Kemal Pasha can be found in Georgia, particularly in Batumi and neighboring villages such as Angisa, Adlia, Feria, Sameba, Kakhaberi, and Charnali. Against this backdrop, it can be inferred that individual families of the first generation of Abkhazi-an emigrants settled further south, not only in Kemal Pasha but possibly in other locations as well.